2017
DOI: 10.1177/2041669517716183
|View full text |Cite
|
Sign up to set email alerts
|

Does Language Influence the Vertical Representation of Auditory Pitch and Loudness?

Abstract: Higher frequency and louder sounds are associated with higher positions whereas lower frequency and quieter sounds are associated with lower locations. In English, “high” and “low” are used to label pitch, loudness, and spatial verticality. By contrast, different words are preferentially used, in Catalan and Spanish, for pitch (high: “agut/agudo”; low: “greu/grave”) and for loudness/verticality (high: “alt/alto”; low: “baix/bajo”). Thus, English and Catalan/Spanish differ in the spatial connotations for pitch.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 30 publications
2
38
0
2
Order By: Relevance
“…Our results are in line with previous findings that suggest the existence of a perceptual (or representational) link between loudness and spatial verticality (Bruzzi et al, 2017;Eitan & Granot, 2006;Eitan et al, 2008;Fernandez-Prieto et al, 2017). Specifically, the pattern of results found in the present study also implies that this link is stronger (or even limited to) for the association between loud sounds and high spatial positions than for the association between quiet sounds and low positions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with previous findings that suggest the existence of a perceptual (or representational) link between loudness and spatial verticality (Bruzzi et al, 2017;Eitan & Granot, 2006;Eitan et al, 2008;Fernandez-Prieto et al, 2017). Specifically, the pattern of results found in the present study also implies that this link is stronger (or even limited to) for the association between loud sounds and high spatial positions than for the association between quiet sounds and low positions.…”
Section: Discussionsupporting
confidence: 93%
“…In this way, participants were instructed to respond based on the arbitrary relationship between loudness and colour, without the explicit implication of a linguistic label directly related to verticality. This allowed us to avoid a possible linguistic confound that could account for the association between loudness and verticality (see Fernandez-Prieto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wegner and Erskine, 2003;Henk Aarts, 2007;Linser and Goschke, 2007;Aarts, Oikawa, and Oikawa, 2010;Wenke, Fleming, and Haggard, 2010;Gentsch and Schütz-Bosbach, 2011;Dewey and Carr, 2012;Sidarus, Chambon, and Haggard, 2013;Damen, van Baaren, and Dijksterhuis, 2014). In the case of implicit SoA, some experiments have shown that primed concepts influence intentional binding reports (e.g., Moore et al, 2009;Aarts and van den Bos, 2011;Aarts et al, 2012;Khalighinejad et al, 2017) as well as sensory attenuation reports (Gentsch and Schütz-Bosbach, 2011;Allenmark et al, 2015;Fernandez-Prieto et al, 2017). It has to be noted that this paper focuses on the criticism of the cue integration theory in the context of explicit SoA reports rather than implicit SoA reports, as I have criticized the implicit SoA operationalizationwhich assumes the debatable cognitive penetration 3 assumption elsewhere.…”
Section: Interface Intentionality and Accuracy Problems Of The Cue mentioning
confidence: 99%
“…For example, in both auditory pitch and spatial elevation, a number of human languages use shared vocabulary across both domains (e.g. 'high'-'low' for both pitch and elevation [10]). Such linguistic pairings may have given rise to intuitive correspondencesor indeed may have arisen from them in the development of language [11].…”
Section: Introductionmentioning
confidence: 99%